Pelatihan Pengambilan Data Di Lapangan Menggunakan GPS Dan Avenza Maps - Anif Farida; Mutiono Mutiono (CV. Multi Kreasi Media, 2023)
The map is a description of the appearance on the surface of the earth, which is very helpful for the user to conduct an initial study of an area. Map sources can come from satellite-based field measurements, namely GPS and Avenza Maps. The purpose of this activity is to increase knowledge and skills in data collection in the field using GPS and Avenza Maps. The method used in this activity is in the form of lectures and direct practice, which is divided into three stages. These stages are observation to identify problems, provision of material about GPS and Avenza Maps, followed by direct practice in the field, and evaluation to determine the success rate of the training. The results of the activity showed that the level of knowledge and understanding of the participants increased, with the indicator that the participants were able to operate both the GPS and the Avenza Maps application themselves when taking coordinates in the field.